Analisis Efektifitas Sistem Informasi Akuntansi dalam Pengelolaan Klaim Asuransi Syariah di Indonesia - Zaky, Husnul; Nurlaila; Fadhila Rahma, Tri Inda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The sharia insurance industry is growing rapidly in Indonesia, but the management of insurance claims still faces challenges related to the effectiveness of accounting information systems. The study aims to analyze the effectiveness of accounting information systems in the management of sharia insurance claims. The research method used is a case study at one of the leading Shariah insurance companies. Data is collected through interviews, observations, and documentation studies. Data analysis is carried out qualitatively with a descriptive approach. The results of the research show that the accounting information system used has been quite effective in supporting the process of sharia insurance claims. However, there are some aspects that need to be improved, such as system integration, data quality, and compliance with Sharia principles. Recommendations to improve the effectiveness of accounting information systems include improving the functionality of systems, improving procedures, as well as enhancing the competence of human resources. Implementation of these recommendations is expected to improve the performance of sharia insurance companies and customer satisfaction.